2020
DOI: 10.3390/met10111517
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Application of Field Dislocation and Disclination Mechanics to Grain Boundaries

Abstract: We review the mechanical theory of dislocation and disclination density fields and its application to grain boundary modeling. The theory accounts for the incompatibility of the elastic strain and curvature tensors due to the presence of dislocations and disclinations. The free energy density is assumed to be quadratic in elastic strain and curvature and has nonlocal character. The balance of loads in the body is described by higher-order equations using the work-conjugates of the strain and curvature tensors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…Achieving large strains and the elaboration of materials with complex microstructures put forward the need to take into account rotational modes of deformation, associated with disclinations. A review of field dislocation and disclination mechanics-a crystal plasticity model suggested about fifty years ago in a form based on continuous distributions of defects and developed to further include here the dynamics of rotational discontinuities-is given in [2]. Furthermore, the paper considers the application of this concept for modeling grain boundary-mediated plasticity.…”
mentioning
confidence: 99%
“…Achieving large strains and the elaboration of materials with complex microstructures put forward the need to take into account rotational modes of deformation, associated with disclinations. A review of field dislocation and disclination mechanics-a crystal plasticity model suggested about fifty years ago in a form based on continuous distributions of defects and developed to further include here the dynamics of rotational discontinuities-is given in [2]. Furthermore, the paper considers the application of this concept for modeling grain boundary-mediated plasticity.…”
mentioning
confidence: 99%